Simultaneous Determination of Phenobarbital, Phenytoin, Carbamazepine and Carbamazepine-10,11-epoxide in Plasma of Epileptic Patients - Azam Samadi; Maryam Khoubnasabjafari; Mohammad Barzegar; Shahram Sadeghvand; Shadi Shiva; Abolghasem Jouyban (Tabriz University of Medical Sciences, 2019)
Background: Quantitative analyses of antiepileptic drugs are required in clinic and to rational dosage adjustment, the clinician needs the blood levels of these drugs. A high-performance liquid chromatography with spectrophotometric detection has been developed and validated for simultaneous determination of some antiepileptic drugs in plasma of patients with epilepsy. Methods: A simple procedure based on deproteinization by acetonitrile was used for pre-treatment of plasma samples. Liquid chromatographic analysis was carried out on a Nova-Pak® C18 analytical column, using a ternary mixture of potassium dihydrogen phosphate buffer (pH 6.0)-acetonitrile-2-propanol (63:22:15, v/v/v) as the mobile phase, at a flow rate of 1.0 mL min-1. Results: Calibration curves were linear over a range of 1-40 µg mL-1 for phenobarbital, 1-30 µg mL-1 for phenytoin, 0.3-15 µg mL-1 for carbamazepine and 0.5-6 µg mL-1 for carbamazepine epoxide. Conclusion: The simple sample pre-treatment, combined with the fast chromatographic run was used for the determination of antiepileptic drugs for a large number of patient samples.